Potentiality of Calotropis procera on the Yield of Biocrudes and Biogas Production - R. Arumugam2*, M. Manikandan1 and (Journal of Phytology, 2010)
The identification of plants rich in hydrocarobons and botanochemicals has gained worldwide interest now-a-days, since they can serve as potential renewable energy resources to alternate fossil fuels. The present study was aimed to screen the potentiality of the latex bearing plant Calotropis procera (L) W.T. Aiton as an alternative source of energy. The bio-crude yield of oil was varied from 1.54 to 3.97% and the polyphenol content was high in stem (S) 4.86% compared to whole plant (WP) (4.00%) and leaf (3.33%). The botanochemicals in the oil fractions were identified by thin layer chromatographic studies (TLC) as sterols, free fatty acids, waxes and hydrocarbons. The IR spectra of hydrocarbon fractions obtained from C. procera exhibited peaks at 2980cm-1 and 1955 cm-1 indicated the presence of C-H structure of methyl or methylene group (CH3 & CH4). The 1H-NMR spectral analysis confirmed the possible presence of potential bioactive compounds such as cis-polyisoprene (natural rubber), trans-polyisoprene (gutta), wax, ester and hydrocarbons. Experiments were also conducted at laboratory scale to evaluate the biomethanation property C. procera. The slurry of cow dung with the C. procera supplement (3:1) were used for the experiment and the results showed increased production of biogas as the age of digester increased over control. The nutrient composition was analysed in the left over slurry after digestion. The results showed that the fertilizer value of the digested slurry effluent in the test digester was significantly higher than the control slurry in terms of organic compounds as well as mineral content.